De novo assembly of the kidney and spleen transcriptomes of the cosmopolitan blue shark, Prionace glauca - Machado A.M. (2018)
Cartilaginous fishes (sharks, rays and chimaeras) comprise a highly diversified group of basal vertebrates occupying a plethora of ecological aquatic niches. They represent critical components of marine ecosystems and food webs, although numerous species are threatened and almost half are poorly known. Genomic resources emerging from this basal jawed vertebrate group have offered valuable insights into the evolution of vertebrate-specific traits. Yet, the taxon remains largely understudied. Here, we generated the first high-quality de novo assembly of kidney and spleen transcriptomes of the blue shark (Prionace glauca). A total of 32,917,412 and 52,666,542 reads were obtained for spleen and kidney, respectively, using RNA-Seq Illumina technology. De novo multi-tissue assembly resulted in 97,317 unigenes with an N50 of 1975 bp, in which 87,571 were assigned to a particular tissue or combination of tissues based on the sequencing read mapping. Functional annotation generated 28,564 and 19,854 open reading frames in spleen and kidney, respectively. This dataset provides a significant resource for physiological and evolutionary studies, namely into the unique osmoregulatory system of Chondrichthyes and the evolution of the immune system in vertebrates. © 2017 Elsevier